Integration Of Islamic Human Rights Principles In The Citizen Charter: A Study On The Fulfillment Of The Right To Life, Dignity, Justice, Equality, And Public Health Rights (A Case Study Of Public Health Services At Mardiwaluyo Regional Hospital And Sananwetan Community Health Center) - Muh. Zainul Ikwan; Asmawi Asmawi; Kojin Kojin; Winarto Winarto (International Journal of Science and Environment (IJSE), 2025)
The Citizen’s Charter focuses on transparency, accountability, and quality public services. Within the framework of Islamic Human Rights, it emphasizes the importance of protecting public interests and achieving impartial social justice, meaning justice without discrimination. Sharia itself aims to attain the welfare (maslahah) of society, aligning with the principles of the Citizen’s Charter. Thus, it can be interpreted as support for initiatives aimed at improving the quality of public health services and fulfilling citizens' rights. Therefore, the principles of justice, transparency, and community welfare are in line with the objectives of the Citizen’s Charter. This study found: 1) The integration of Islamic Human Rights (IHR) into the Citizen’s Charter in the healthcare sector; 2) The formulation, implementation, and evaluation of medical services based on the Citizen’s Charter at Mardiwaluyo Regional Hospital. A qualitative method was used in this study, applying a case study type with a multi-site design. Data analysis used the Miles and Huberman model, including data reduction, data display, verification, and conclusion drawing. The data were analyzed from both single-site and cross-site data. The research findings on the integration of Islamic Human Rights principles in the Citizen’s Charter show that the concept of integrating IHR principles into the Citizen’s Charter in the health service sector develops the concept proposed by Khan and Nasir in Medical Ethics in Islam: Implications for the Citizen’s Charter. The findings expand this into several components: the Right to Quality Health Services, Accessibility, Transparency and Informativeness, Non-Discrimination, Community or Patient Participation in Decision-Making, Accountability, Balanced and Proportional Structuring, and Responsibility — all applied in support of community welfare and quality of life. In terms of Islamic Human Rights, the integration of Islamic medical ethics principles with the Citizen’s Charter creates a healthcare service that is ethical, transparent, just, and patient-centered. By incorporating Islamic moral values such as rahmah (compassion), amanah (trust), adl (justice), and hifz al-‘ird (protection of dignity), the implementation of the Citizen’s Charter can be more effective and sustainable. The formulation stage of Citizen’s Charter-based medical services from the IHR perspective involves four stages: formulation, service implementation, and service evaluation. One notable finding is the promotion phase — including the promotional efforts conducted by both Mardiwaluyo Regional Hospital and the Sananwetan Community Health Center.